Wavelets and their applications - Misiti, Michel (Digital signal and image processing series., 2007)
The last fifteen years have seen an explosion of interest in wavelets with applications in fields such as image compression, turbulence, human vision, radar and earthquake prediction. Wavelets represent an area that combines signal in image processing, mathematics, physics and electrical engineering. "Wavelets and their Applications" is intended for the wide audience that is interested in mastering the basic techniques, such as decomposition and compression.